INCLUSIVE COMMUNICATION STRATEGIES IN EQUALITY CAMPAIGNS FOR THE DEAF COMMUNITY: A CASE STUDY OF THE SUNYI BERMAKNA COMMUNITY IN EAST KUTAI REGENCY, EAST KALIMANTAN, INDONESIA - Handi Wijaya; La Mani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the inclusive communication strategies used by the Sunyi Bermakna (Meaningful Silence) community in campaigning for equality for the deaf in East Kutai. Using a qualitative case study approach, the research explores the practice of inclusive communication through in-depth interviews, observation, and document analysis. The findings show that Sunyi Bermakna utilizes sign language, visual media, social campaigns, and digital platforms to disseminate messages of equality. These strategies not only raise public awareness but also strengthen the position of the deaf community within an inclusive social environment. This study emphasizes the importance of inclusive communication in community public relations to foster understanding, reduce marginalization, and encourage social change.